Continuous production of hydroxyapatite Pickering emulsions using a mesostructured reactor - Ribeiro, Andreia (2018)
Emulsions are used in a wide range of applications, including food and cosmetics. Nowadays, the demand for sustainable products has increased with Pickering emulsions emerging as clean alternatives. To achieve the industrial implementation of Pickering emulsions, continuous production and less intensive energy devices are required. In this context, a mesostructured reactor based on an innovative static mixer, NETmix, was tested to produce Pickering emulsions from a previously developed formulation in batch mode. The effect of the number of cycles (2–35) and Reynolds number (200–500), parameters that influence the residence time and the quality of mixing, on the Pickering emulsion properties (average droplet size, droplet morphology, and stability) was studied. The obtained results pointed out the feasibility of using NETmix to produce Pickering emulsions. It is a versatile technique to control in a tailor-made way the droplet size and generate small droplets at short times. Results show a decrease of the droplet size with increasing number of cycles and Reynolds. Under the tested conditions, stable dispersions with droplet size of ∼7 μm were produced using 17 cycles and Re = 400. Microscopy images show an oil core and nano-hydroxyapatite shell morphology.